2006
DOI: 10.1002/anie.200600154
|View full text |Cite
|
Sign up to set email alerts
|

A Self‐Complementary Assembly of Metallamacrocycles Directed by RuCl⋅⋅⋅HN Hydrogen Bonds and Its Reversible Dichotomy by Halide Anions in Solution

Abstract: The coordination-directed self-assembly approach is an extremely powerful strategy for the synthesis of various 2-and 3D metallasupramolecules and can provide a structural and functional basis for its potential application toward molecular sensing and catalysis by using supramolecular chemistry.[1] In particular, discrete 3D self-assemblies derived from the multiple noncovalent interactions between monomeric metallo-subunits, such as chains, squares, and/or cages, are very intriguing because they are structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…A search of the Cambridge Crystallographic Database (CSD, version 5.39, update May 2018; Groom et al, 2016) reveals eight structures with the H 2 L 1 skeleton. These include the methyl pyridinium compound of H 2 L 1 (Dorazco-Gonzá lez et al, 2010), two Ru + compounds (Park et al, 2006;Mishra et al, 2012), two Pd 2+ compounds (Qin et al, 2002(Qin et al, , 2003 and two Co 2+ compounds (Singh et al, 2010(Singh et al, , 2011. There is only one Mn 2+ coordination compound (Noveron et al, 2003), with bis(hexafluoroacetylacetonato) as an ancillary ligand.…”
Section: Database Surveymentioning
confidence: 99%
“…A search of the Cambridge Crystallographic Database (CSD, version 5.39, update May 2018; Groom et al, 2016) reveals eight structures with the H 2 L 1 skeleton. These include the methyl pyridinium compound of H 2 L 1 (Dorazco-Gonzá lez et al, 2010), two Ru + compounds (Park et al, 2006;Mishra et al, 2012), two Pd 2+ compounds (Qin et al, 2002(Qin et al, , 2003 and two Co 2+ compounds (Singh et al, 2010(Singh et al, , 2011. There is only one Mn 2+ coordination compound (Noveron et al, 2003), with bis(hexafluoroacetylacetonato) as an ancillary ligand.…”
Section: Database Surveymentioning
confidence: 99%
“…17 This is unusual in that the halide anions on metal ions are often lost during self-assembly processes at the expense of coordinating donor ligands. A further case in point is the report of Park et al who described formation of a tennis ball structure 21 2 that simultaneously exploits co-ordination-directed and anion recognition of metal halides.…”
Section: Structure and Assemblymentioning
confidence: 99%
“…A later report by Park et al . showed that a pyridylamide‐ligand‐bridged Ru(II) cyclic loop complex self‐associates to a dimerized structure by the formation of hydrogen bonds between the amide N─H and Ru─Cl moieties with additional intermolecular π–π and CH–π stabilizing interactions . We envision that the incorporation of a pyridyl‐substituted pyridine 2,6‐dicarboxamide into a positively charged, transition‐metal‐directed, self‐assembled macrocylic framework would bring all the essential elements for anion binding including electrostatic, hydrogen‐bonding, conformation‐matching, and aromatic π–π interactions into one molecule.…”
Section: Introductionmentioning
confidence: 99%